Burden-sharing in a Changing Climate: Which Principles and Practices can Theologians Endorse? - Russell, Cathriona (Studies in Christian ethics, 2011)
Empirical evidence of our changing climate is frequently interpreted through the lens of either optimism or pessimism. In tandem with this, ethical responses can oscillate from myopic ‘business as usual’ to misanthropic ‘lifeboat ethics’. In this paper I argue that these are inadequate and unworthy positions from which to begin in Christian ethics. The question of sharing the burdens of climate-change mitigation and adaptation is the crucial task facing the world community. The development of the burden-sharing rules—sector based as well as country based—since the Kyoto agreement will be evaluated from the perspective of three theological ethical principles: justice, solidarity and subsidiarity. Lastly I suggest that creation serves as a ground for developing shared perspectives in the ethics of environmental questions in the context of intercultural and interfaith dialogue.